Peningkatan Kapasitas Manajemen Sumber Daya Manusia (Msdm) Pada Pemilik Toko Pertanian Di Kecamatan Panjalu, Kabupaten Ciamis - Erna Rusmiwati Sukandar; Ridwan Hakiki (CV. SINAR HOWUHOWU, 2026)
Panjalu District is one of the regions in Ciamis Regency with significant agricultural potential. This potential has driven the growth of agricultural supply stores (kios saprotan) as key providers for farmers' needs. However, the majority of agricultural stores in this area are still managed traditionally, particularly within the aspect of Human Resource Management (HRM). The primary challenges faced include the absence of a clear division of labor, family-based employee management lacking key performance indicators, and a deficiency in customer service skills. This community service activity aims to provide training and mentoring in implementing basic HRM functions. The methods utilized include interactive lectures, case studies, and assistance in drafting a simple Standard Operating Procedure (SOP). The results of this activity indicate a 75% increase in the partners' understanding regarding the importance of professionalism at work, alongside the formulation of a draft for service SOPs and an adaptive division of labor tailored for agricultural stores in Panjalu.